Protection of Data in Cloud Computing using Image Processing - Watermarking Technique - Thaiyalnayaki, S; Devi, S (International Journal of Computer Sciences and Engineering, 2025)
Abstract--With the dawn of easiness in manipulating and transferring digital data in today’s world, insuring digital image integrity has therefore become a major issue. One solution to this problem is to embed watermark in the digital data, i.e. Digital watermarking. Usually watermarking has been used in currency notes, government documents, passport for security features and stamp papers for legal purpose. Watermarking is very beneficial for identifying the document of any authorized person. Digital watermarking emerged as a solution for copyrights detection, protection and maintenance of important data. Millions of private images are generated in various digital devices every day. Cloud computing, one of the most important computing paradigms emerged in recent years. Watermarking techniques to ensure data privacy. Consequently, this framework will increase the speed of development on ready-to-use digital humanities tools